2016
DOI: 10.1051/0004-6361/201527737
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotic theory of gravity modes in rotating stars

Abstract: Context. The seismology of early-type stars is limited by our incomplete understanding of gravito-inertial modes. Aims. We develop a short-wavelength asymptotic analysis for gravito-inertial modes in rotating stars. Methods. The Wentzel-Kramers-Brillouin approximation was applied to the equations governing adiabatic small perturbations about a model of a uniformly rotating barotropic star. Results. A general eikonal equation, including the effect of the centrifugal deformation, is derived. The dynamics of axis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 39 publications
0
39
0
Order By: Relevance
“…N, but is less appropriate if |σ| " 2Ω, as discussed in Mathis (2009). Its validity domain, not well defined, remains essentially limited to the regime of super-inertial waves (Prat et al 2016). It is represented in Fig.…”
Section: Discussion Of Physical Assumptionsmentioning
confidence: 99%
“…N, but is less appropriate if |σ| " 2Ω, as discussed in Mathis (2009). Its validity domain, not well defined, remains essentially limited to the regime of super-inertial waves (Prat et al 2016). It is represented in Fig.…”
Section: Discussion Of Physical Assumptionsmentioning
confidence: 99%
“…The pulsation description of rotating stars is at least a twodimensional problem (e.g., Prat et al 2016). However, it is possible to reduce this dimensionality into two separate onedimensional (1D) problems for the radial (Lee & Saio 1986) and angular dependence (Lee & Saio 1997;Townsend 2003b) of eigensolutions.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in [17], low-frequency gravito-inertial waves are trapped near the equatorial plane, but can propagate near the centre, which is not accounted for by the traditional approximation. In the limit of very low frequencies (ω f ), the trapping implies that…”
Section: Low-frequency Approximationmentioning
confidence: 99%
“…Such an asymptotic theory has been built for acoustic waves ( [15]) and has led to the prediction of regularities in corresponding spectra of fast-rotating stars ( [16]). For gravito-inertial waves, a first study ( [17]) has allowed us to constrain the structure of the phase space. In particular, we have shown that it is dominated by nearly integrable structures at low frequencies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation